Effect of effective microorganism on paddy seedling growth / Nurnadirah Mat Nawi - Mat Nawi, Nurnadirah (Faculty of Plantation and Agrotechnology, 2015)
This study was conducted at UiTM Jasin, Melaka, during September to December 2014. The study is to determine the effect of difference Effective Microorganisms (EM) rates on radical emergence and growth of paddy seedlings and to identify the most suitable concentration for seed treatment. The experiment was carried out with four levels of seed treatments. Tl = 1:10 dilution of EM, T2 = 1:20 dilution of EM, T3 = 1:50 dilution of EM and T4 = pure water (control). The seeds were soaked for four days before being sown immediately. The result showed that the treatment T3 got highest seedling height, germination percentage, number of tillers and fresh and dry weight of root compare to other treatment s. Considering 1:50 dilution of EM found to be most suitable concentration in this study for better and consistent performance of seedlings growth. However, there was no significant difference between EM treatment and control in most parameters that have been measured.